Norms governing urban African American adolescents’ sexual and substance-using behavior - Dolcini, M. Margaret (2012)
Using a probability-based neighborhood sample of urban African American youth and a sample of their close friends (N = 202), we conducted a one-year longitudinal study to examine key questions regarding sexual and drug using norms. The results provide validation of social norms governing sexual behavior, condom use, and substance use among friendship groups. These norms had strong to moderate homogeneity; and both normative strength and homogeneity were relatively stable over a one-year period independent of changes in group membership. The data further suggest that sex and substance using norms may operate as a normative set. Similar to studies of adults, we identified three distinct “norm-based” social strata in our sample. Together, our findings suggest that the norms investigated are valid targets for health promotion efforts, and such efforts may benefit from tailoring programs to the normative sets that make up the different social strata in a given adolescent community.